Tissue factor-induced fibrinogenesis mediates cancer cell clustering and multiclonal peritoneal metastasis. (28th January 2023) - Miyazaki, Makoto; Nakabo, Ayaka; Nagano, Yoshiko; Nagamura, Yuko; Yanagihara, Kazuyoshi; Ohki, Rieko; Nakamura, Yoshikazu; Fukami, Kiyoko; Kawamoto, Jun; Umayahara, Kenji; Sakamoto, Masaru; Iwaya, Keiichi; et al.
Abstract: Peritoneal metastasis is one of the most frequent causes of death in several types of advanced cancers; however, the underlying molecular mechanisms remain largely unknown. In this study, we exploited multicolor fluorescent lineage tracking to investigate the clonality of peritoneal metastasis in mouse xenograft models. When peritoneal metastasis was induced by intraperitoneal or orthotopic injection of multicolored cancer cells, each peritoneally metastasized tumor displayed multicolor fluorescence regardless of metastasis sites, indicating that it consists of multiclonal cancer cell populations. Multicolored cancer cell clusters form within the peritoneal cavity and collectively attach to the peritoneum. In vitro, peritoneal lavage fluid or cleared ascitic fluid derived from cancer patients induces cancer cell clustering, which is inhibited by anticoagulants. Cancer cell clusters formed in vitro and in vivo are associated with fibrin formation. Furthermore, tissue factor knockout in cancer cells abrogates cell clustering, peritoneal attachment, and peritoneal metastasis. Thus, we propose that cancer cells activate the coagulation cascade via tissue factor to form fibrin-mediated cell clusters and promote peritoneal attachment; these factors lead to the development of multiclonal peritoneal metastasis and may be therapeutic targets. Highlights: Multicolor lineage tracking reveals the multiclonal origin of peritoneal metastasis. Cancer cell clusters formed in the abdomen are the source of peritoneal metastasis. Fibrin fibers mediate cancer cell clustering and attachment to the peritoneum. Tissue factor expressed by cancer cells drives fibrinogenesis in the abdomen. Tissue factor is required for cancer cell clustering and peritoneal metastasis.